The Role of Reading and Computing initiative (RAMP) in developing some of reading skills among the First Three Grades pupils in Wadi Al-Sair District from the teachers perspective - Al-Harby, Seetah Ali (Journal of Educational and Psychological Sciences, 2020)
The study aimed to explore the Role of Reading and Mathematics initiative (RAMP) in developing some of reading skills among the First Three Grades pupils in Wadi Al-Sair District from the teachers perspective and the years of experience and the teacher qualification. The study based on the Descriptive Approach the Researcher used questionnaire to collect data which consist of (22) paragraph divided to (5) areas. The study community was all of the teachers of the First Three Grades (225)the sample was (120) female teachers and(14) male teachers. The result showed that The Role of Reading And Computing initiative (RAMP) in developing reading skills was high and there is statistically significant difference on the level of the whole tool refers to the years of experience(10 years and more) and the effect of qualification has statistically significant difference (master degree).